Micromolding of three-dimensional components - Hung, W. N. P.; Ngothai, Y.; Yuan, S.; Lee, C. W.; Ali, Mohammad Yeakub (Kluwer Academic Publishers, 2001)
This paper presented a new technique to fabricate 3D microcomponents. The simulation and molding of microgears of 70-1000μm diameters and 1:1 aspect ratio were completed. Micro-EDM was combined with focused ion beam sputtering to produce a microcavity for subsequent molding process. The simulation pinpointed locations of trapped gas, predicted filling time, stress distribution, and uniformity of a microgear. Subtle differences in simulation results were observed depending on the finite elements used. Limited success was found for predicting weld lines and surface finish. The molded microcomponents producing by this technique possessed features that were compatible with those fabricated by the LIGA technique, i.e., surface finish ~10 nm, accuracy < 1 μm, and aspect ratio >10.